Reframing The Significance of Interfaith Classes in Islamic Education - Uswatun Hasanah; Yoga Anjas Pratama; Khoirul Umam Addzaky (Ta’dib : Jurnal Pendidikan Islam, 2025)
This study reconceptualizes interfaith classes within Islamic education using maqāṣid al-sharīʿah and adab as its core analytical framework. Employing a qualitative library study, relevant literatures were systematically reviewed using a reflective content analysis approach. The findings indicate that interfaith classes contribute to Islamic education in three keyways: strengthening socio-religious competence through respectful communication and empathy; countering radicalism by fostering dialogue, critical reflection, and solidarity; and enhancing global competence through the development of cross-cultural skills and inclusive leadership. This study highlights interfaith education as a theologically grounded and pedagogically strategic approach for cultivating moderate, globally engaged Muslims committed to peace and social justice